2013
DOI: 10.1038/pcan.2013.8
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the order of critical alterations in prostate cancer development and progression by IHC: further evidence that PTEN loss occurs subsequent to ERG gene fusion

Abstract: Background ERG rearrangements and PTEN loss are two of the most common genetic alterations in prostate cancer. However, there is still significant controversy regarding the order of events of these two changes during the carcinogenic process. We used IHC to determine ERG and PTEN status and calculated the fraction of cases with homogeneous/heterogeneous ERG and PTEN staining in a given tumor. Methods and Results Using a single standard tissue section from the index tumor from radical prostatectomies (N= 77),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
60
0
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(68 citation statements)
references
References 36 publications
7
60
0
1
Order By: Relevance
“…10 In the current cohort, prostate cancer tumors had more heterogeneous results in PTEN FISH compared with TMPRSS2/ERG FISH. Similar findings were reported using IHC assessment 17 : most ERG-positive radical prostatectomy samples had homogeneous ERG staining, whereas more than half of the PTEN loss samples had heterogeneous staining. Together, these observations support the theory that TMPRSS/ERG rearrangement is an early event of prostate carcinogenesis, whereas PTEN deletion is more likely a later event and hence associated with advanced diseases.…”
Section: Discussionsupporting
confidence: 74%
“…10 In the current cohort, prostate cancer tumors had more heterogeneous results in PTEN FISH compared with TMPRSS2/ERG FISH. Similar findings were reported using IHC assessment 17 : most ERG-positive radical prostatectomy samples had homogeneous ERG staining, whereas more than half of the PTEN loss samples had heterogeneous staining. Together, these observations support the theory that TMPRSS/ERG rearrangement is an early event of prostate carcinogenesis, whereas PTEN deletion is more likely a later event and hence associated with advanced diseases.…”
Section: Discussionsupporting
confidence: 74%
“…Tumor fusion status is not associated with lethal progression in most studies (22), but our group recently presented the first evidence that tumor fusion status may modify the association of prostate cancer risk factors with lethal prostate cancer progression (23). PTEN loss is more common in fusion-positive compared with fusion-negative disease (10,(24)(25)(26)(27), and PTEN loss almost certainly occurs subsequent to ERG rearrangement (19,28,29). Thus, presence of the TMPRSS2:ERG gene fusion may modify the effects of PTEN loss on disease progression.…”
Section: Articlementioning
confidence: 99%
“…PTEN is most commonly lost by deletion, which is frequently a focal and subclonal event in primary prostate tumors (10,19,20), making reliable detection difficult by methods requiring nucleic acid extraction or fluorescence in situ hybridization (FISH). Addressing this issue, our group previously optimized an immunohistochemistry (IHC) assay for in situ PTEN protein detection in prostate cancer (6).…”
Section: Articlementioning
confidence: 99%
“…This significant finding remained after adjusting for clinical variables and further supports the role of ERG and PTEN in PCa progression, but did not reach statistical significance when evaluating the loss of PTEN protein expression in the same manner as above mentioned combinations with PTEN deletion. The sequential order of ERG rearrangements and PTEN aberrations is currently unsolved but [6,[19][20][21] concurrent ERG rearrangement and PTEN loss have been shown to promote PCa [5,6] and have been associated with PCa outcome. Leinonen et al found that patients harboring aberrant ERG with simultaneous PTEN loss, were associated with shorter progression-free survival [8] and Yoshimoto et al, found the combination to be predictive of earlier biochemical recurrence [7], supporting the results found in this study.…”
Section: Discussionmentioning
confidence: 99%